TMT’s Impact on Company Performance: Unraveling the Role of Strategic HRM Choices - Magdalena Majowska (European Management Studies)
Purpose: The article explores the intricate relationship between top management teams (TMTs), strategic HRM, and company performance. It investigates whether TMT attributes influence strategic HRM choices, ultimately contributing to improved company performance. The study introduces mediation models to unravel how two TMT strategic HRM choices mediate the relationship between TMT attributes and company performance. Design/Methodology/Approach: Conducting a nationwide study involving 150 Polish companies, the research collected data through surveys with 150 HR managers and 150 top managers. Statistical methods, including descriptive statistics, correlations, and regression analysis, were employed in the analytical framework to explore the hypothesized relationships. Findings: The study uncovers a positive correlation between TMT attributes and company performance. It identifies TMT emphasis on SHRM and curatorship of HR as pivotal mediators, showing that larger, diverse TMTs are inclined to prioritize gaining a competitive advantage through human resources, and address vulnerability challenges, positively impacting overall company performance. Research Limitations/Implications: Acknowledging limitations in the oversight of organizational processes, particularly translating top managers’ choices into company performance, the article highlights the need for further validation of the curatorship of HR measurement tools, and suggests incorporating objective financial data for comprehensive performance assessments in future research. Originality and Value: The study contributes valuable insights into the complex dynamics impacting company performance, examining key TMT attributes, and introducing the concept of “curatorship of human resources”. The novel perspective, alongside TMT emphasis on SHRM, proves pivotal in positively influencing overall performance, filling a significant gap in HRM literature.